2006
DOI: 10.1002/jcp.20871
|View full text |Cite
|
Sign up to set email alerts
|

Functional expression of voltage‐gated sodium channels in primary cultures of human cervical cancer

Abstract: Cervical cancer (CaC) is the third most frequent cause of death from cancer among women in the world and the first in females of developing countries. Several ion channels are upregulated in cancer, actually potassium channels have been suggested as tumor markers and therapeutic targets for CaC. Voltage-gated sodium channels (VGSC) activity is involved in proliferation, motility, and invasion of prostate and breast cancer cells; however, the participation of this type of channels in CaC has not been explored. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
75
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 49 publications
3
75
1
2
Order By: Relevance
“…Voltagegated Na + channels (Na V ) are abnormally expressed in cancer cells from different epithelial origins (e.g. breast, lung, prostate, colon and cervix) and, in melanoma, their function might be associated with cancer progression (Diaz et al, 2007;Hernandez-Plata et al, 2012;House et al, 2010;Roger et al, 2006;Roger et al, 2007;Yildirim et al, 2012). The Na V 1.5 isoform (also known as SCN5A) is overexpressed in breast cancer tissues, is associated with the development of metastases and is functional in highly invasive breast cancer cells (Fraser et al, 2005;Roger et al, 2003;Yang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Voltagegated Na + channels (Na V ) are abnormally expressed in cancer cells from different epithelial origins (e.g. breast, lung, prostate, colon and cervix) and, in melanoma, their function might be associated with cancer progression (Diaz et al, 2007;Hernandez-Plata et al, 2012;House et al, 2010;Roger et al, 2006;Roger et al, 2007;Yildirim et al, 2012). The Na V 1.5 isoform (also known as SCN5A) is overexpressed in breast cancer tissues, is associated with the development of metastases and is functional in highly invasive breast cancer cells (Fraser et al, 2005;Roger et al, 2003;Yang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Voltage-gated Na + channels (Na v ), normally associated with cellular excitability, have been found to play crucial roles in metastatic behaviours of several cancers, including breast Fraser et al, 2005;Gao et al, 2009;Gillet et al, 2009;Roger et al, 2003), prostate (Abdul and Hoosein, 2002;Bennett et al, 2004;Diss et al, 2001;Diss et al, 2005;Grimes et al, 1995;Laniado et al, 1997;Nakajima et al, 2009;Smith et al, 1998), cervical (Diaz et al, 2007), colon (House et al, 2010), ovarian (Gao et al, 2010), SCLC (Blandino et al, 1995;Onganer and Djamgoz, 2005;Onganer et al, 2005;Pancrazio et al, 1989) and NSCLC (Roger et al, 2007). In prostate cancer, functional expression of Na v enhances cellular migration, invasion and endocytosis (Ding et al, 2008;UysalOnganer and Djamgoz, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…One key step is the acquisition by cancer cells of an invasive potency, mainly relying on the capacity to degrade basement membranes and extracellular matrices (Gupta and Massague, 2006) by various proteases such as matrix metalloproteinases (Egeblad and Werb, 2002) or cysteine cathepsines (Mohamed and Sloane, 2006). We and others have shown that voltage-gated sodium channels (Na V ) are abnormally expressed in cancer cells of epithelial origin and associated with cancer progression (Laniado et al, 1997;Roger et al, 2003Roger et al, , 2006Roger et al, , 2007Fraser et al, 2005;Diaz et al, 2007). In the highly invasive MDA-MB-231 breast cancer cell line, Na V 1.5 activity enhances extracellular matrix invasion by increasing the activity of acidic cysteine cathepsins B and S through an acidification of the pericellular microenvironment (Gillet et al, 2009).…”
Section: Introductionmentioning
confidence: 99%